2007
DOI: 10.1038/sj.bjc.6604115
|View full text |Cite
|
Sign up to set email alerts
|

The E-cadherin repressor Snail is associated with lower overall survival of ovarian cancer patients

Abstract: Epithelial ovarian cancer is the leading cause of death among female genital malignancies. Reduced expression of the cell adhesion molecule E-cadherin was previously shown to be associated with adverse prognostic features. The role of the E-cadherin repressor Snail in ovarian cancer progression remains to be elucidated. We analysed formalin-fixed and paraffin-embedded specimens of 48 primary ovarian tumours and corresponding metastases for expression of E-cadherin and Snail by immunohistochemistry. We found a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 42 publications
5
101
2
Order By: Relevance
“…Several studies have demonstrated that nuclear localization of Snail correlates with tumor progression, with enhanced Snail immunoreactivity in metastatic lesions (70,71). Furthermore, patients with both primary and metastatic tumors positive for Snail expression showed a significant decrease in overall survival (72). LRP6 functions as a Wnt coreceptor that recruits Axin and Dishevelled to the plasma membrane, thereby disrupting the degradation of ␤-catenin and facilitating ␤-catenin nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that nuclear localization of Snail correlates with tumor progression, with enhanced Snail immunoreactivity in metastatic lesions (70,71). Furthermore, patients with both primary and metastatic tumors positive for Snail expression showed a significant decrease in overall survival (72). LRP6 functions as a Wnt coreceptor that recruits Axin and Dishevelled to the plasma membrane, thereby disrupting the degradation of ␤-catenin and facilitating ␤-catenin nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Snail was first identified as the most important transcriptional repressor of E-cadherin [43] . Snail can down-regulate expression of E-cadherin, inducing EMT and promoting cell migration and invasion [22,44] . Overexpression of Snail was detected in various tumor cell lines, including breast, pancreatic and gastric cancers [45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of TNF-α-induced invasiveness-associated genes expression by GA Considering that Snail regulates the expression of invasiveness-associated genes, such as E-cadherin, MMP-9, and fibronectin [21,22] , we determined whether GA could regulate the expression of invasiveness-associated genes in TNF-α-stimulated PC3 cells. It was demonstrated that TNF-α-treated PC3 cells exhibited up-regulated mRNA and protein expression levels of both MMP-9 and fibronectin.…”
Section: Wwwnaturecom/aps Lü L Et Almentioning
confidence: 99%
“…Snail immunoreactivity in metastases was found to correlate with higher grade and reduced E-cadherin expression. A subsequent study by Blechschmidt et al (2008) on 48 primary ovarian neoplasms and 50 metastases found Snail immunoreactivity in 37.5% and 52%, respectively. A borderline significant difference in overall survival with Snail expression in metastases was noted.…”
Section: Neoplasms Of the Genitourinary Tractmentioning
confidence: 99%